Ultrasound features of Cytotoxic venomous snake bite and implications for surgical management - A systematic review - Karundat Bhola; Samson Mashele; Yoshan Moodley (Student's Journal of Health Research, 2022)
Background: Snake bite is an important, yet often neglected health problem in many regions of the world. Cytotoxic venomous snake bites (VSB) have the potential to induce significant tissue injury, resulting in compartment syndrome. This research sought to provide a summary of ultrasound features of VSB, with the aim of improving management in afflicted patients. Methods: A systematic review of 2 electronic medical literature databases was performed. Pre-defined eligibility criteria were used to identify relevant published case series (sample size 10 or more) which reported on ultrasound features of VSB. Screening of the reference lists of eligible manuscripts was also performed. Results: Two case series reporting on ultrasound studies of cytotoxic VSB were included in this review. One study was from the United States and the other study was from South Africa. Children under 12 years comprised a large proportion of VSB victims (92.3% in the American study and 33.3% in the South African study). The majority of VSB victims were male (76.9% in the American study and 57.1% in the South African study). Snake species involved were Crotaline/rattlesnakes (American study) and adders or cobras (South African study). In both studies, VSBs were located on the upper limbs. The most common ultrasound finding in both studies was subcutaneous oedema. The deep muscular appears to be minimally affected in cytotoxic VSB. Conclusion:  Ultrasound features of cytotoxic envenomation were consistent between studies. Ultrasonography provides useful information which can be used to supplement the information obtained during the external clinical examination of cytotoxic VSB and can be used to identify patients with a risk of compartment syndrome who might require surgery. Recommendation: Ultrasonography should be performed as one of the primary investigations when patients present with VSB.